NEW DATA ON THE BASEMENT OF THE WESTERN PART OF THE SIBERIAN CRATON - Pevzner V.S.; Krinin V.A.; Malich N.S.; Chukhonin A.P.; Zinchenko V.N. (My University, 1988)
The basement of the western part of the Siberian craton was penetrated to below 3798 m in the Kochumdek No. 3 well, drilled in the Turukhansk district, between the Lower Tunguska and the Bakhta Rivers, in the field occupied by Permian-Triassic volcanic rocks. Our work has confirmed the concept of block structure of the basement in the western part of the Siberian craton, where Archean blocks are separated by eucratonic geosutures of Late Archean-Early Proterozoic age, such as protoaulacogens and rifts. These geosutures form a mobile framework in the basement that predetermined many features of the tectonic evolution, igneous activity and ore deposition in the craton cover.
Keywords: Triassic; Proterozoic; Archean; Permian; Precambrian::Archean; Mesozoic::Triassic; Precambrian::Proterozoic; Мезозой::Триасовая; Палеозой::Пермская; Докембрий::Архей; Paleozoic::Permian; Докембрий::Протерозой